2017
DOI: 10.1371/journal.pone.0184858
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association of MRI determined subclinical cardiovascular disease with dizziness and vertigo in a cross-sectional population-based study

Abstract: ObjectiveWe investigated the association between subclinical cardiovascular diseases assessed by MRI examination and symptoms of dizziness and vertigo in participants of a population-based sample.MethodsData from 400 participants (169 women) aged from 39 to 73 of a cross-sectional MRI sub-study of the “Kooperative Gesundheitsforschung in der Region Augsburg” (KORA) FF4 study from the south of Germany was used. MRI determined subclinical cardiovascular diseases include left and right ventricular structure and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…Apart from subjective memory loss, in our preliminary study, we found that a substantial proportion of patients with headaches, dizziness had cognitive decline using global cognitive tests. Headache, dizziness and memory loss are the most common unspecific complaints in middle-aged patients of neurology clinics, which have been considered as characteristic of cerebrovascular insufficiency due to CSVD such as WMLs 20 21. In accordance with our preliminary study, it was reported that headache disorders were associated with a 24% greater risk of all-cause dementia 22.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…Apart from subjective memory loss, in our preliminary study, we found that a substantial proportion of patients with headaches, dizziness had cognitive decline using global cognitive tests. Headache, dizziness and memory loss are the most common unspecific complaints in middle-aged patients of neurology clinics, which have been considered as characteristic of cerebrovascular insufficiency due to CSVD such as WMLs 20 21. In accordance with our preliminary study, it was reported that headache disorders were associated with a 24% greater risk of all-cause dementia 22.…”
Section: Introductionsupporting
confidence: 80%
“…Among these non-acute ischaemia symptoms, headache, dizziness and memory loss are the most common symptoms accompanied with or without other symptoms in the ageing population. Also, headaches, dizziness and memory loss are all reported to be associated with cerebral ischaemia and cognitive decline 19–22 24 48…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the study population of this MRI substudy, which included the whole cohort, is not representative due to the enrichment of prediabetic and diabetic subjects. However, additional analyses using weights accounting for differences between the MRI substudy and the whole study cohort did not reveal any substantial dissimilarity [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…As the KORA-MRI sub-study focused on individuals without overt cardiocerebrovascular disease 39 , the study sample is not entirely representative of the general population. Participants with prediabetes and diabetes are likely to be over-represented in this cohort which may have favored the selection of diabetes-related variables based on the increased power to detect a diabetes-related effect.…”
Section: Discussionmentioning
confidence: 99%